2017
DOI: 10.1167/iovs.16-21138
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Outer Retinal Band Three Investigated With Adaptive-Optics Optical Coherence Tomography

Abstract: PurposeOptical coherence tomography's (OCT) third outer retinal band has been attributed to the zone of interdigitation between RPE cells and cone outer segments. The purpose of this paper is to investigate the structure of this band with adaptive optics (AO)-OCT.MethodsUsing AO-OCT, images were obtained from two subjects. Axial structure was characterized by measuring band 3 thickness and separation between bands 2 and 3 in segmented cones. Lateral structure was characterized by correlation of band 3 with ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…In healthy individuals, the bright spots at the height of the PR inner segment-outer segment (IS/OS) junction and from the cone OS tips (COST) result in a dense pattern in AO-OCT en face images, which actually represents the PR mosaic. [19][20][21][22][23][24][25] This mosaic is similar to that obtained with AO-SLO and AO fundus camera (AO-FC). 20,22,26 In contrast to the latter modalities, AO-OCT has the advantage of a significantly higher axial resolution (more than an order of magnitude) and the ability to create full threedimensional volumetric image data of the retina.…”
supporting
confidence: 79%
“…In healthy individuals, the bright spots at the height of the PR inner segment-outer segment (IS/OS) junction and from the cone OS tips (COST) result in a dense pattern in AO-OCT en face images, which actually represents the PR mosaic. [19][20][21][22][23][24][25] This mosaic is similar to that obtained with AO-SLO and AO fundus camera (AO-FC). 20,22,26 In contrast to the latter modalities, AO-OCT has the advantage of a significantly higher axial resolution (more than an order of magnitude) and the ability to create full threedimensional volumetric image data of the retina.…”
supporting
confidence: 79%
“…In albino mice, which lack melanin in RPE cells, a thin highly reflective band corresponding to Bruch's membrane (BrM) appears posterior to IS/OS. The mouse retina layer assignments presented here are based on our understanding of the cellular origins of light scattering in the human retina presented by Jonnal et al 38,39 and correlations with mouse retinal histology. Figure 3 shows directional reflectivity profiles measured for four major retinal layers of three mice strains.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of the anatomical origins and properties of the outer retinal bands have shown that they are broader than would be predicted by the thin reflectors hypothesized to exist at IS/OS and COST [ 36 ], and that one of the factors in their broader appearance may be the axial staggering of surfaces among neighboring cells combined with lateral blur [ 32 , 37 ]. Table 1 shows how estimates of this axial staggering may depend upon the chosen method of flattening.…”
Section: Resultsmentioning
confidence: 99%